Stress, adversity quotient, and health behaviors of undergraduate students in a Thai university during COVID-19 outbreak - Bovornpot Choompunuch; Jiraporn Sonsroem; Siripong Kutawan; Atittiya In-udom; Wanich Suksatan (Belitung Nursing Journal, 2021)
Background: University students are an essential human resource for national development. Thus, it is important to study the stress, adversity quotient, and health behaviors of these students during the COVID-19 pandemic.Objective: This study aimed to identify stress, adversity quotient, and health behaviors and examine the relationship between these factors in undergraduate students during the COVID-19 outbreak.Methods: The current study was a quantitative study with a cross-sectional design. A total of 416 undergraduate students in a Thai university were selected using a convenience sampling technique. A questionnaire was used to collect the data on stress, adversity quotient, and health behaviors of undergraduate students during the COVID-19 outbreak. Data were analyzed using mean, standard deviation, and Pearson’s Product Moment Correlation Coefficient.Results: This study indicated that stress was at a high level (3.54 ± .53; Mean ± SD), adversity quotient was at a high level (3.77 ± .63; Mean ± SD), and health behaviors were at a moderate level (3.06 ± .53; Mean ± SD). The current study also found that stress and adversity quotient were irrelevant. Stress and health behaviors were negatively correlated with a level of significance of .01 (r = -.31), and adversity quotient and health behaviors were positively correlated with a level of significance of .01 (r = .051).Conclusion: It is suggested that healthcare providers, families, and professors should consider stress and adversity quotient in developing interventions to promote healthy behaviors in terms of physical and psychological factors in university students.